2015
DOI: 10.3109/09513590.2014.1003293
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes on fertility issues in breast cancer patients: an Italian survey

Abstract: Background: Fertility issues should be discussed with young women before the start of any anticancer treatment. The study is aimed to investigate the attitude on fertility among Italian oncologists and breast surgeons dealing with BCa, and to report the consensus achieved on specific statements. Methods: One hundred and sixty-two panelists anonymously expressed an opinion through a web-based platform on 19 statements based on the Delphi method. Results: Ninety-one percent of oncologists considered important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
(34 reference statements)
0
27
0
1
Order By: Relevance
“…However, similar to other studies [18, 19, 20], there is still a subset of patients who do not have fertility discussions, which suggests the frequency of fertility discussions is sub-optimal in clinical settings. Prior research has highlighted oncologists' lack of knowledge towards fertility preservation options among one of the reasons contributing to a lack of fertility discussions [21]. One interesting finding from our study highlights the family medicine physician as a potential source of fertility information in Portugal.…”
Section: Discussionmentioning
confidence: 71%
“…However, similar to other studies [18, 19, 20], there is still a subset of patients who do not have fertility discussions, which suggests the frequency of fertility discussions is sub-optimal in clinical settings. Prior research has highlighted oncologists' lack of knowledge towards fertility preservation options among one of the reasons contributing to a lack of fertility discussions [21]. One interesting finding from our study highlights the family medicine physician as a potential source of fertility information in Portugal.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, oncologists face several barriers to have this discussion, including lack of knowledge and safety concerns, insufficient resources and lack of linkage with reproductive units [33]. As recently shown in an Italian survey, 93% of medical oncologists acknowledged having poor insight into the subject, more than 80% were not in favor of performing a hormonal manipulation for cryopreservation procedures, and 90% underscored a lack of coordination between oncology and reproductive units [12]. The PREFER-FERTILITY study aims to support and to improve the discussion around fertility issues among oncologists and patients before treatment with the ultimate goal to implement the referral of young women interested in fertility preserving procedures to reproductive unit.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo/oocyte cryopreservation, cryopreservation of ovarian tissue and the use of temporary ovarian suppression with luteinizing hormone-releasing hormone analogs (LHRHa) during chemotherapy are the available options to preserve fertility in breast cancer patients [11]. Despite a growing literature on this topic over the past years, there are still several obstacles limiting the access to fertility preservation procedures [11, 12]. Moreover, very limited data are available on the number of patients that take active steps towards the available strategies for fertility preservation and on the reasons for refusal of these procedures after oncofertility counseling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Italian survey showed that 46% of the surveyed oncologists believed that pregnancy affects the prognosis of young women with breast cancer, and 49% supported the statement that an increase in estrogen levels during pregnancy might stimulate the growth of hidden cancer cells 16 . Similarly, 30% of the physicians responding to the BCY3 survey agreed or were neutral on the statement that pregnancy in breast cancer survivors may increase the risk of recurrence 12 .…”
Section: Impact Of Breast Cancer On Future Pregnancies and Fertility mentioning
confidence: 95%